Effortful Control and Interpersonal Behavior in Daily Life. Issue 3 (4th May 2019) - Cain, Nicole M.; Meehan, Kevin B.; Roche, Michael J.; Clarkin, John F.; De Panfilis, Chiara
ABSTRACT: The Cognitive-Affective Processing System (CAPS) was used to examine effortful control (EC) as a moderator of daily interpersonal behavior. Participants ( N = 240) were nonclinical young adults who completed a 7-day event-contingent experience sampling study of interpersonal perception and affect. Multilevel linear models indicated that EC moderated within-person covariation of interpersonal warmth and affect activation; high EC individuals reported greater momentary warm behaviors when perceiving others as affectively activated. EC also amplified between-person covariation of interpersonal warmth between self and others; high EC individuals generally responded to perceptions of another's warmth with a greater degree of warm behavior. Varying levels of EC predict responses to interpersonal perceptions and affect in daily life, suggesting an important dimension for interpersonal functioning.